Surface arsenic speciation of a drinking-water treatment residual using X-ray absorption spectroscopy - Sarkar, Dibyendu; Parsons, Jason G.; Datta, Rupali K.; Gardea-Torresdey, Jorge Luis; Makris, Konstantinos C. (My University, 2007)
Drinking-water treatment residuals (WTRs) present a low-cost geosorbent for As-contaminated waters and soils. Previous work has demonstrated the high affinity of WTRs for As, but data pertaining to the stability of sorbed As is missing. Sorption/desorption and X-ray absorption spectroscopy (XAS), both XANES (X-ray absorption near edge structure) and EXAFS (extended X-ray absorption fine structure) studies, were combined to determine the stability of As sorbed by an Fe-based WTR. Arsenic(V) and As(III) sorption kinetics were biphasic in nature, sorbing >90% of the initial added As (15,000 mg kg−1) after 48 h of reaction. Subsequent desorption experiments with a high P load (7500 mg kg−1) showed negligible As desorption for both As species, approximately <3.5% of sorbed As; the small amount of desorbed As was attributed to the abundance of sorption sites. XANES data showed that sorption kinetics for either As(III) or As(V) initially added to solution had no effect on the sorbed As oxidation state. EXAFS spectroscopy suggested that As added either as As(III) or as As(V) formed inner-sphere mononuclear, bidentate complexes, suggesting the stability of the sorbed As, which was further corroborated by the minimum As desorption from the Fe-WTR.
Keywords: Residuals; Drinking water; Stability; Arsenic (As); XANES; EXAFS; Remediation